Paradoxical leadership and organizational support in the new normal era: An experimental vignette study virtual team collective efficacy - Dharma, Gani; Parahyanti, Endang (Universitas Negeri Padang, 2023)
Implementation of Working from Home (WFH) or hybrid (WFH and Work from Office) during the COVID-19 pandemic has been known to remain until the end of the pandemic. In spite of that, the implementation of WFH or Hybrid is known to have an impact on interfering with the team functionality that works virtually at the company. Therefore, there needs to be an effort to increase the virtual team’s collective efficacy (VTCE) when collaborating virtually. One of the antecedents that could increase the VTCE is Paradoxical Leadership Behavior (PLB), a leadership style that could combine two competing behaviors into one new behavior, in this case combining the roles of agentic and communal leadership as a whole. Additionally, the Perceived Organizational Support (POS) is an employee’s perception of the organization's effort in increasing welfare and providing support at work are also antecedents from VTCE. Both antecedents are required to be further examined by utilizing vignette experiment 2 (high vs low PLB) x 2 (high vs low POS) between-subject design on 256 employees conducting WFH or hybrid. Utilizing 2 x 2 ANOVA Factorial, a significant effect was revealed from PLB and POS on VTCE. The implication of this research showed that there needs to be an implementation of PLB and post-pandemic organization support to increase the VTCE for the team when conducting WFH or hybrid.